Microcontroller-based Soft Starter and Overcurrent Detector for Enhancing Performance of Induction Motor - Lestiana, Leila; Muchlas, Muchlas; Sutikno, Tole (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
When an induction motor starts up, it draws a large current, which can damage it and cause a voltage dip effect that interferes with other electrical equipment. The machine, however, has numerous applications, particularly in the industrial sector, due to its low cost, robustness, and dependability. Induction motor performance must be improved to reduce starting current surges and protect against overcurrent. Thyristors are used in the developed system to control the voltage level. The microcontroller's trigger pulse causes a ramp-up in supply voltage, resulting in a soft-starting effect in a 1-phase induction motor. The system detects overcurrent using the popular current sensor module. This research results in a high-performing soft starter and overcurrent detector. When compared to supplying the motor directly online, the soft-starter unit can reduce the starting current by 55%. Meanwhile, the embedded overcurrent detector performs admirably, accurately detecting motor overcurrent and cutting off the power supply when the motor reaches overcurrent.